Sir William Muir's discourse on the Prophethood of Muhammad (PBUH) : a critical assessment - Kabir, Aliyu (Kulliyyah Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
Prophethood of Muhammad (PBUH) has been a controversial discourse in the history of Christian-Muslim relations. Sir William Muir (1819-1905) was among prominent Christian scholars who wrote extensively on this subject. The primary aim of this research is to examine and evaluate the issue as reflected in Muir's compendium The Life of Muhammad from Original Sources (1923). By adopting descriptive, historical, analytical and comparative methods, the research exhibits the fact that polemics were the hallmark of many Christian attitudes to historical Islam from its early relationship with Islam until the modern era. Although there were some positive outlooks with regard to the Christian attitudes towards Islam in general and Prophet Muhammad in particular in the modern era, the works of Muir, however, continue to echo remnants of early Christian apprehension towards the Prophet Muhammad (PBUH) based on hatred and prejudice. Muir's three important discourses namely: revelation, character and polygamy of the Prophet, once scrutinised are proven to be totally and completely at loggerheads with the Islamic viewpoint.